Speech Acts in the Lyrics of 'About You' by The 1975: A Semantic Study - Novemty Tampubolon; Bernike Anggita Ristia Damanik (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2026)
This study examines the types and illocutionary forces of speech acts in the song "About You" by The 1975 using John Searle's taxonomy (assertives, directives, commissives, expressives, declarations). A qualitative descriptive method was applied to the lyrical text. The analysis reveals that the 18 lines contain 20 illocutionary occurrences. Expressives dominate with 45%, conveying longing, regret, and nostalgia. Assertives account for 35%, providing narrative context about past relationships and the speaker's emotional state. Directives and commissives each constitute 10%; directives appear exclusively as rhetorical questions expressing anxiety rather than seeking information, while commissives include conditional promises and metaphorical commitments. Declaratives are absent, as expected in lyrical discourse. Hybrid speech acts where one line performs multiple illocutionary functions are identified as a distinctive feature. Linguistic devices such as repetition, parallelism, rhetorical questions, metaphor, and ellipsis enhance illocutionary force, transforming the lyrics into a performance of remembrance. The findings are compared with previous research on emotionally charged lyrics, showing consistency with expressive-dominant songs. This study contributes to literary pragmatics, the semantics-pragmatics interface, and the discourse analysis of music, offering a replicable framework for analyzing speech acts in song lyrics.